2008
DOI: 10.1088/0022-3727/41/23/235409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface passivating ligand on structural and optoelectronic properties of polymer : CdSe quantum dot composites

Abstract: We demonstrate the effect of surface passivation of cadmium selenide quantum dots (CdSe QDs) (∼5–7 nm) by tri-n-octylphosphene-oxide (TOPO) and oleic acid (OA) on the structural and optoelectronic properties of their respective polymer : CdSe composites by dispersing them in poly(2-methoxy-5(2-ethylhexyloxy)-1,4-phenylinevinylene) and poly(3-hexylthiophene) polymers. It has been found that OA passivated-QDs (∼7 nm), as compared with TOPO passivated CdSe QDs (∼5 nm), are of (i) high quality that provide better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…For this purpose, the passivation of the surface of the QDs has been carefully studied in order to minimize the traps and to provide a barrier with the surrounding medium [27], and hence to provide an enhancement of the emission efficiency [28]. Indeed, colloidal nanocrystals are usually characterized by temperature-insensitive emission, because the barriers are so high that thermal energy losses are inhibited.…”
Section: Emission Of Lightmentioning
confidence: 99%
“…For this purpose, the passivation of the surface of the QDs has been carefully studied in order to minimize the traps and to provide a barrier with the surrounding medium [27], and hence to provide an enhancement of the emission efficiency [28]. Indeed, colloidal nanocrystals are usually characterized by temperature-insensitive emission, because the barriers are so high that thermal energy losses are inhibited.…”
Section: Emission Of Lightmentioning
confidence: 99%
“…These are balanced by the stabilizing repulsive interactions that originate from i) the steric stabilization layer consisting of the PS-COOH 20 surfactant on each particle, and ii) the TOPO coordinating stabilizer. Since the molar mass and the grafting density of the sterically dominating PS-COOH surfactant are similar for all samples, it is reasonable to conclude that the steric repulsion by the polymer is not responsible for the observed differences in 25 self-assembled structures. While the contour length of a TOPO layer is about 1 nm, 22 the thickness of a grafted PS-COOH layer can be estimated according to the blob-based model of Biver 23 for polymer brushes on curved surfaces as approximately 8 -10 nm.…”
Section: Resultsmentioning
confidence: 87%
“…No indication is found for the presence of a crystalline CoO phase neither in X-ray diffraction nor in electron diffraction experiments. 25 In order to get a better insight into the dynamic nature of the 30 chain formation and the structures present in dispersion, we perform static (SLS) and dynamic light scattering (DLS) experiments on particle dispersions in toluene. Light scattering experiments for magnetic nanoparticles are scarce due to their high absorption, and in order to reduce this effect measurements 35 are carried out at very low sample concentrations (~ 3 x 10 -3 wt.-%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CdSe QDs had diameters between 3.1 and 3.9 nm with a deviations ± 0.2 nm, and an optical absorption spectral of about 450 nm. Kumari et al [23] have demonstrated that CdSe QDs (5 ~ 7 nm) with TOPO and oleic acid (OA) have a good surface passivation and optoelectronic properties.…”
Section: Quantum Dot (Qd) Structures: Pbse-qd Cdse Colloidal Qds CDmentioning
confidence: 99%